Synergetic effect of temperature and humidity on the leakage of KOH electrolyte and related reliability of zinc-air batteries - Rao, Jyothsna Murli; Yadav, Abhijeet; Conseil-Gudla, Helene; Ambat, Rajan (Frontiers in Materials, 2022)
The Zinc-air primary batteries (ZAB’s) are prone to electrolyte leakage upon exposure to high temperature and humidity conditions. Potassium hydroxide is a hygroscopic and corrosive compound and it can cause various electrochemical corrosion failures for the attached electronics inside a device. In this study, the effect of temperature and humid conditions on the leakage of Potassium hydroxide electrolyte from three different Zinc Air Battery variants were investigated. The batteries were exposed to hot and humid conditions, and a qualitative Gel test with pH indicator was used to visually observe the leakage from the individual set of battery variants. The residues of the released electrolyte was identified by FTIR and quantified using a titration method. SEM-EDS analysis was also performed to examine the surface of the batteries and sealants for eventual damage. The related effect of electrolyte leakage on the reliability of the batteries was performed by a voltage discharge test. The hygroscopicity properties of pure Potassium hydroxide were studied using a water sorption/desorption equipment and was correlated with electro impedance spectroscopy analysis using an interdigitated test board. The results from the study indicate that the increase in temperature caused an increased amount of electrolyte leakage under saturated humid conditions. Leakage of Potassium hydroxide electrolyte caused damage to the sealant gasket, clogged the oxygen ventilation holes of the batteries, and exhibits high hygroscopic properties when exposed to high temperature and humid conditions.